(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The child mortality rate is thought to be a sensitive measure of a nation's health and well-being. International organizations and national governments have acknowledged the need to emphasize their efforts to increase child survival. Inequality in child health in India is seen on a number of levels. In India, there is evidence of inequality in a number of areas related to child health, according to several sources. Data on children who have ever been born and kids who have ever survived were collected from India's 2011 census. In the majority of Assam districts, child mortality rates significantly decreased. The districts of Udalguri, Kokrajhar, Dhubri, Hailakandi, and Darrang are still very distant. Tinsukia and Dibrugarh have demonstrated improvements above their prior performance. Situation in rural areas is better than it was five years ago. In order to achieve the right fix by various developmental goals, more effort should be put forward to lower the child death rate.